Effects of 6-week sprint interval training compared to traditional training on the running performance of distance runners: a randomized controlled trail - Jin, Kai; Cai, Mengbiao; Zhang, Yongqian; Wu, Bin; Yang, Yi (Frontiers in Physiology, 2025)
IntroductionThis study aimed to compare the effects of sprint interval training versus traditional training on running performance in well-trained male distance runners.MethodsTwenty male distance runners (VO2: 67.4 ± 4.5 mL/kg/min, personal best time for the 5000 m: 14′38″47 ± 00′23″46) were recruited and randomly assigned to either the intervention training (IT) group, which performed sprint interval training, or the control training (CT) group, which engaged in traditional long-distance training. Both groups completed their respective training regimens twice a week for 6 weeks. Measurements for VO2max, O2 cost, time to exhaustion (TTE), and running times for 100, 400, and 3000 m were taken before and after the intervention.ResultsThe results indicated that the IT group showed significant improvements in TTE and running performance across 100, 400, and 3000 m (all P < 0.01), while the CT group only demonstrated improvements in 400 m time (P < 0.01). The IT group exhibited superior 3000 m performance compared to the CT group (P < 0.01). Analysis of effect sizes revealed small to moderate improvements in physiological and performance measures for the IT group, with VO2max showing a small effect size of 0.43, O2 cost a moderate effect size of 0.65, and TTE a moderate effect size of 0.77.ConclusionThese findings suggest that sprint interval training may offer superior benefits for enhancing running performance of well-trained male distance runners, particularly in time to exhaustion and middle-to long-distance events, compared to traditional longdistance training.